Virtualização de servidor com base em pequena empresa - Brixel, Alexandre de Oliveira (2018)
The objective of this work is to optimize the internal network of the Music Producer Company CANJA Produções Musicais in a fast way, functional, safe, easy maintenance and with low cost. Among the procedures to be applied are server virtualization using the Linux operating system, Citrix XenServer software, and service configuration, to optimize physical space and low-cost hardware. The services that will be installed are: DHCP, FTP, Proxy, DNS and Firewall.